"Easy But Not Simple"—Nursing Students' Descriptions of the Process of Care in a Psychiatric Context. (2nd January 2016) - Looi, Git-Marie Ejneborn; Sävenstedt, Stefan; Engström, Åsa
Abstract : The nurse-patient interaction is the cornerstone of psychiatric care, yet the concept "mental health nursing" is difficult to describe. This article aims to address this problem through the experiences of nursing students. Online journals from 14 nursing students were analyzed using qualitative content analysis, resulting in three categories: Trusting the Trusting Relationship, Voicing the Unspoken Needs, and Balancing the Dynamics of Doing and Being. This study demonstrates that providing nursing care based on trusting relationships is not a demanding task, but it takes place in a complex environment that has a tendency to make easy things complicated.